Evaluation of energy consumption and noise reduction change of a strengthened building: An educational building case - Dicle, Seda Yuksel; Zoroglu, Fatma; Atmaca, Ahmet Bircan; Akdag, Nese Yuruk; Gedik, Gulay Zorer (YILDIZ TECHNICAL UNIV, 2024)
The buildings in various geographical conditions are strengthened due to different reasons, such as earthquakes, fire, or deterioration. One of the important issues is that comfort levels are ensured, and energy consumption is kept at a minimum in educational buildings where renovation and strengthening work is being carried out. In this study, in terms of energy consumption and acoustic comfort, a method is proposed to examine a building damaged in an earthquake and then strengthened. The method has also been created and implemented to provide control and improvement suggestions in terms of thermal and acoustic conditions in strengthening projects of buildings. As a case study, the pre- and post-reinforcement situation of an educational building in a temperate humid climate has been evaluated. In addition, different glazing scenarios that reduce energy consumption while increasing facade noise reduction have been developed and analyzed. The results showed that while sufficient noise reduction is achieved in the building envelope, there is a 15.9% reduction in the total energy consumption of the building. The optimum scenario decreased total energy consumption by 19.4 % in B113 and 26 % in B114 and increased the facade noise reduction levels by 14.2 dB in B113 and 15 dB in B114. The proposed method and the findings will contribute to the design process of newly designed, renovated, and strengthened buildings in terms of energy efficiency and indoor acoustical comfort.
Keywords: Blassroom; Educational Building; Energy Efficient Design; Noise Reduction Level; Strengthened Buildings; COMFORT; PERFORMANCE; CLASSROOMS; DESIGN; Engineering